Responsive Polymer Brush Design and Emerging Applications for Nanotheranostics - Li, Danyang; Xu, Lizhou; Wang, Jing; Gautrot, Julien E. (Advanced healthcare materials, 2021)
Responsive polymer brushes are a category of polymer brushes that are capable of conformational and chemical changes in response to external stimuli. They offer unique opportunities for the control of bio−nano interactions due to the precise control of chemical and structural parameters such as the brush thickness, density, chemistry, and architecture. The design of responsive brushes at the surface of nanomaterials for theranostic applications has developed rapidly. These coatings can be generated from a very broad range of nanomaterials, without compromising their physical, photophysical, and imaging properties. Although the use of responsive brushes for nanotheranostic remains in its early stages, in this review, the aim is to present how the systems developed to date can be combined to control sensing, imaging, and controlled delivery of therapeutics. The recent developments for such design and associated methods for the synthesis of responsive brushes are discussed. The responsive behaviors of homo polymer brushes and brushes with more complex architectures are briefly reviewed, before the applications of responsive brushes as smart delivery systems are discussed. Finally, the recent work is summarized on the use of responsive polymer brushes as novel biosensors and diagnostic tools for the detection of analytes and biomarkers. Responsive polymer brushes offer unprecedented control of the coating physico‐chemistry and molecular architecture for the design of nanomaterials for the delivery of therapeutics and their simultaneous imaging and biomonitoring. Polymer brushes with precisely controlled responsive and bioactive properties are attractive candidates for the design of the next generation of nanotheranostic platforms.